A single‐center, pilot study evaluating a novel TriHex peptide‐ and botanical‐containing eye treatment compared to baseline. (16th April 2018) - Reivitis, Alex; Karimi, Kian; Griffiths, Chester; Banayan, Ashley
Summary: Background: Topical treatments containing tripeptide and hexapeptide (TriHex technology) have been proven to contribute to youthful skin by clearing the extracellular matrix and stimulating collagen and elastin production. Objective: Evaluate the efficacy of a novel eye treatment containing TriHex peptides and other synergistic ingredients for the daily treatment of fine lines/crow's feet around the eyes, under eye hollowing, under eye bags, and dark circles. Patients/Methods: In this study, 10 subjects (9 female and 1 male) aged 30‐60 of Fitzpatrick skin type I, II, or III were selected to use an eye treatment containing TriHex peptides and active botanicals (Alastin Restorative Eye Treatment with TriHex Technology™, ALASTIN Skincare, Inc., Carlsbad, CA) twice daily for 12 weeks. Subjects were photographed and evaluated at baseline, week 4, week 8, and week 12 by a board‐certified facial plastic surgeon. Using an adjusted Griffiths scale (0 = none, best possible condition and 9 = severe, worst possible condition), subjects were evaluated on severity of fine lines/crow's feet, under eye hollowing, under eye bags, and dark circles at each visit. Subjects completed a "Subject Questionnaire" at week 4, week 8, and week 12 pertaining to the subject's observations and perceived improvement of these measures. Results: Based on the investigator's assessments, overall improvement in periocular skin was noted for all 10 subjects. Over the course of 12 weeks, raw scores significantly decreased indicating reduction of lines/crow's feet (41% improvement), under eye hollowing (29% improvement), under eye bags (48% improvement), and dark circles (39% improvement). Based on the "Subject Questionnaire, " all subjects noted overall improvement of the appearance of skin around the eyes. Conclusion: Based on the findings of this study, this eye treatment containing TriHex peptides and active botanicals is an effective stand‐alone treatment for the rejuvenation of periocular skin. When used twice daily, this product can reduce the appearance of lines/crow's feet, under eye hollowing, under eye bags, and dark circles.